Single Leg Bridge Test is Not a Valid Clinical Tool to Assess Maximum Hamstring Strength - Gabriela Bissani Gasparin; João Breno Araujo Ribeiro-Alvares; Bruno Manfredini Baroni (International Journal of Sports Physical Therapy)
# Background